2019
DOI: 10.1111/iej.13177
|View full text |Cite
|
Sign up to set email alerts
|

Stem/progenitor cell‐mediated pulpal tissue regeneration: a systematic review and meta‐analysis

Abstract: Background Stem/progenitor cell‐mediated pulpal regeneration could represent a promising therapeutic alternative in the field of clinical endodontics. Aim The present study aimed to systematically assess and meta‐analyse dental pulpal tissue regeneration, pulpal vitality and apical healing after the transplantation of stem/progenitor cells versus no transplantation. Data sources MEDLINE, Cochrane CENTRAL and EMBASE were searched up to January 2019 for animal experiments and human trials evaluating the pulpal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The literature reports advantages of using cell transplantation, such as the ability to control cell number and cell type (subpopulation of stem cells) (Fawzy El-Sayed et al 2019). UC-MSCs encapsulated in a PPP matrix are a cell-based treatment option that have provided major management of factors such as a defined amount of UC-MSCs (10 6 ) from a single donor.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports advantages of using cell transplantation, such as the ability to control cell number and cell type (subpopulation of stem cells) (Fawzy El-Sayed et al 2019). UC-MSCs encapsulated in a PPP matrix are a cell-based treatment option that have provided major management of factors such as a defined amount of UC-MSCs (10 6 ) from a single donor.…”
Section: Discussionmentioning
confidence: 99%
“…Stem/progenitor cells are characterized by their outstanding differentiation potential into multiple types of specialized cell lineages, relying on their pluri-or multipotency, while maintaining their self-replicating ability [1][2][3][4][5][6][7][8][9][10]. Among the different stem/progenitor cell types, mesenchymal stem/progenitor cells (MSCs) have been widely used in tissue engineering, cell transplantation, and immunotherapy [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…There have been several systematic reviews concerning stem-cell-based pulp regeneration [ 39 , 40 , 41 ]. The previous systematic reviews identified pulp and dentin regeneration in their included studies using in situ stem cell transplantation strategies [ 39 , 40 , 41 ], as in this study. The present scoping review included several more current studies based on eligibility criteria than the previous systematic reviews.…”
Section: Discussionmentioning
confidence: 99%